Involuntary intoxication caused by vaping the synthetic cannabinoid ADB-BUTINACA: A case report - Elise M.A. Slob; Maryam Lyousoufi; Sharif Pasha; Erik B. Wilms (Toxicology Reports)
Synthetic cannabinoids are gaining popularity globally and detection is not commonly available. We report a 27-year-old man who was admitted to the emergency room because of sudden headache, nausea, vertigo, red eyes and palpitations. He confirmed that he had been vaping an electronic cigarette (e-cigarette) earlier that day just before the onset of his symptoms. Despite all negative results in the point-of-care test for recreational drugs, the liquid chromatography-quadrupole time-of-flight mass spectrometry (LC-QTOF-MS) analysis showed that the liquid of the e-cigarette contained ADB-BUTINACA, a synthetic cannabinoid. LC-QTOF-MS represents a significant advancement in the field of drug detection, offering higher sensitivity, specificity, and a broader spectrum of detectable substances. Clinicians should be aware that besides the harmful effects of nicotine and toxic metals in e-cigarettes, e-cigarettes may also contain synthetic cannabinoids or other recreational drugs including new psychoactive substances (NPS), which can cause involuntary intoxication with potentially severe adverse effects. When clinical presentation and/or initial recreational drugs testing results are inconclusive, additional testing with LC-QTOF-MS can be valuable.